Perawatan Pompa Ballast Guna Menunjang Kelancaran Operasional di Kapal MT. Layar Arthawibawa - Vinceciius Ari Setyawan; Dedtri Anwar; Fajar Sutopo (Politeknik Pelayaran Sulawesi Utara, 2024)
In the use of sea transportation, the good condition of the ship has a great influence on the process of ship operation. Its very important because ballast pumps on ships are one of the service systems on ships that are used to dispose of and fill ballast water. The ballast pump system is intended to adjust the level of tilt and draft of the vessel, as a result of changes in load ship so that the stability of the ship can be maintained and to reduce the swaying of the ship caused by waves or large enough squares. As well as the efforts that must be made to maximize on board even what influence is caused by no maintenance on board. The data sources obtained are data obtained directly from the research location by means of observation methods and with qualitative data. The results of the study have shown that many factors cause less optimal ballast pump maintenance Efforts must be made so that ballast pump maintenance is optimal in MT. Layar Arthawibawa is to implement PMS regularly, and there must be a sense of responsibility to all crew members and support from the company itself.